Methylation levels at selected CpG sites in the factor VIII and FGFR3 genes, in mature female and male germ cells - El Maarri, Osman (1998)
Transitional mutations at CpG dinucleotides account for approximately a third of all point mutations. These mutations probably arise through spontaneous deamination of 5-methylcytosine. Studies of CpG mutation rates in disease-linked genes, such as factor VIII and FGFR3, have indicated that they more frequently originate in male than in female germ cells. It has been speculated that these sex-biased mutation rates might be a consequence of sex-specific methylation differences between the female and the male germ lines. Using the bisulfite-based genomic-sequencing method, we investigated the methylation status of the human factor VIII and FGFR3 genes in mature male and female germ cells. With the exception of a single CpG, both genes were found to be equally and highly methylated in oocytes and spermatocytes. Whereas these observations strongly support the notion that DNA methylation is the major determining factor for recurrent CpG germ-line mutations in patients with hemophilia and achondroplasia, the higher mutation rate in the male germ line is apparently not a simple reflection of sex-specific methylation differences.